Nitidine chloride suppresses epithelial‐mesenchymal transition and stem cell‐like properties in glioblastoma by regulating JAK2/STAT3 signaling. (31st March 2021) - Jia, Mingbo; Wang, Ying; Guo, Yingxue; Yu, Pengyue; Sun, Ying; Song, Yanke; Zhao, Liyan
Abstract: Glioblastoma is the most aggressive and common intracranial malignant tumor, and the prognosis is still poor after various treatments. Based on the poor prognosis of glioma, new drugs that suppress the rapid progression and aggressive growth of glioma are urgently needed. It has been reported that nitidine chloride (NC) can inhibit tumor growth and epithelial‐mesenchymal transition (EMT), and EMT is associated with cancer stem cell properties. The present study aimed to investigate the inhibitory effect of NC on the EMT process and stem cell‐like properties in glioma cells. The results showed that the migration and invasion abilities in U87 and LN18 glioma cells were significantly increased after the induction of EMT and these effects were inhibited by NC in a concentration‐dependent manner. NC treatment decreased the expression of EMT markers in glioma cells and self‐renewal capacity of glioma stem‐like cells. We demonstrated that these effects of NC were achieved via JAK2/STAT3 signaling. Taken together, these results indicate that NC inhibits the EMT process and glioma stem‐like properties via JAK2/STAT3 signaling pathway, suggesting that NC may be a potential anti‐glioma drug. Abstract : NC can inhibit the EMT process and glioma stem cell characteristics of glioma cells via modulation of JAK2/STAT3 signaling, suggesting that NC may be a potential anti‐glioma drug.